2017
DOI: 10.1016/j.jacc.2017.07.712
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Cardiac Resynchronization Therapy With or Without Defibrillation in Patients With Nonischemic Cardiomyopathy

Abstract: In patients with NICM, CRT-D was superior to CRT-P in +MWF but not -MWF. These findings have implications for the choice of device therapy in patients with NICM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 26 publications
0
38
0
5
Order By: Relevance
“…A recent observational study including 252 patients with DCM and CRT found that CRT-D provided survival benefit over CRT-P only in those with LGE 29. Additionally, absence of LGE is associated with greater CRT response 30…”
Section: The Emerging Risk Stratification Method: Late Gadolinium Enhmentioning
confidence: 99%
“…A recent observational study including 252 patients with DCM and CRT found that CRT-D provided survival benefit over CRT-P only in those with LGE 29. Additionally, absence of LGE is associated with greater CRT response 30…”
Section: The Emerging Risk Stratification Method: Late Gadolinium Enhmentioning
confidence: 99%
“…Higher CFR also has been suggested to be predictive of CRT response 24 ; thus, sMBF may correlate with better response to CRT. Importantly, while some have suggested that CRT may reduce the need for ICDs in nonischemics, late gadolinium enhancement (LGE) on cardiac MR (CMR) may predict mortality even in patients who have been treated with CRT 25 . Similarly, in our study, lower sMBF was able to identify a high‐risk group despite our cohort's high rate of CRT (49%).…”
Section: Discussionmentioning
confidence: 53%
“…When individual coronary arteries were analyzed, only the LCx was more commonly affected by significant CAD in HF patients with LVEF ≤ 35% when compared to controls (50.0% vs. 7.1%, p = 0.011). At the same time, when LGE was assessed in segments according to coronary artery distribution, there was a trend to more commonly observed LGE in segments supplied by the LAD in HF patients with LVEF ≤ 35% than in controls (68.2% vs. 35.7%, p = 0.056; Table 3).…”
Section: Comparison Of Hf Patients With Lvef Of 35% or Less And Contrmentioning
confidence: 88%
“…Previous studies have found a significant correlation between total scar burden and non-response to CRT, and have proposed a dose-response type relationship in these groups, which may predict this outcome [33,34]. A recent study including patients with dilated cardiomyopathy and CRT found that CRT-defibrillators provided a survival benefit over CRT-pacemakers only in patients with observed LGE [35]. Moreover, implantation of an LV lead over an area with transmural myocardial scarring may result in an ineffective CRT [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation